2020
DOI: 10.1371/journal.pone.0227139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multi-drug resistant bacteria on economic and clinical outcomes of healthcare-associated infections in adults: Systematic review and meta-analysis

Abstract: Background Infections with multidrug resistant (MDR) bacteria in hospital settings have substantial implications in terms of clinical and economic outcomes. However, due to clinical and methodological heterogeneity, estimates about the attributable economic and clinical effects of healthcare-associated infections (HAI) due to MDR microorganisms (MDR HAI) remain unclear. The objective was to review and synthesize the evidence on the impact of MDR HAI in adults on hospital costs, length of stay, and mortality at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
105
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 52 publications
3
105
1
3
Order By: Relevance
“…The positive findings obtained in this study provide hope for the development of novel antimicrobials with cheap production costs from plants against methicillin-resistant S. aureus and multidrug-resistant P. aeruginosa as outlined in the sixty-eighth World Health Assembly [ 18 ]. This will lower the mortality rates and economic impact associated with these drug-resistant infections in most developing countries [ 52 , 53 ]. Moreover, several studies have established evidence that the major causes of fatal diarrhoea and bacteria-associated enterocolitis included methicillin-resistant S. aureus [ 54 ] and multidrug-resistant P. aeruginosa [ 55 , 56 ]; however, our study findings have shown effectiveness of the crude seed extracts of A. heterophyllus against these same superbugs making it a suitable and cheap alternative remedy to be used in treatment .…”
Section: Discussionmentioning
confidence: 99%
“…The positive findings obtained in this study provide hope for the development of novel antimicrobials with cheap production costs from plants against methicillin-resistant S. aureus and multidrug-resistant P. aeruginosa as outlined in the sixty-eighth World Health Assembly [ 18 ]. This will lower the mortality rates and economic impact associated with these drug-resistant infections in most developing countries [ 52 , 53 ]. Moreover, several studies have established evidence that the major causes of fatal diarrhoea and bacteria-associated enterocolitis included methicillin-resistant S. aureus [ 54 ] and multidrug-resistant P. aeruginosa [ 55 , 56 ]; however, our study findings have shown effectiveness of the crude seed extracts of A. heterophyllus against these same superbugs making it a suitable and cheap alternative remedy to be used in treatment .…”
Section: Discussionmentioning
confidence: 99%
“…The growing risk of disease from antibiotic-resistant bacteria is now a global public health concern [ 18 ]. The spread of antibiotic resistance is caused, in part, from the extensive and indiscriminate use of antibiotics, which leads to the emergence of antibiotic-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…These infections are directly related to care and are considered among the most common and preventable adverse events [2]. NIs place a significant burden on patients and hospital staff as they result in medical complications, prolonged hospital stays, high rates of morbidity and mortality, and reduced quality of life; they also place a significant burden on healthcare systems as they result in extra costs related to the extended hospitalization or readmission of patients, patient's care-related expenses and costs involved in limiting further contagion [3][4][5][6][7]. Similar to other nations, Canada has not solved the problem of NIs.…”
Section: Introductionmentioning
confidence: 99%